If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 5 + -9 = 3x + -15 Reorder the terms: 5 + -9 + 2x = 3x + -15 Combine like terms: 5 + -9 = -4 -4 + 2x = 3x + -15 Reorder the terms: -4 + 2x = -15 + 3x Solving -4 + 2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -4 + 2x + -3x = -15 + 3x + -3x Combine like terms: 2x + -3x = -1x -4 + -1x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -4 + -1x = -15 + 0 -4 + -1x = -15 Add '4' to each side of the equation. -4 + 4 + -1x = -15 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -15 + 4 -1x = -15 + 4 Combine like terms: -15 + 4 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| -3=18-x | | 2n+5=4(n+2)-a | | p-6p=-4 | | 4y-9=13 | | 2y+6x=-14 | | n+17=35 | | n+25=30 | | x^3+14x^2+52x+21=0 | | -26+5x=-1 | | 58-2x=16x+16 | | 15000+7x=1210+9x | | 1/6(6x-3)=6(2+x)-5x | | x-6=0.666(x-3) | | 3x^2-6x+4= | | -1.25+2.3x=1.51 | | V=800(5/20) | | 8-3x=-4 | | 6+12=-79-7x | | 15x^4y^2/5x^3y^2 | | -4(-3p+7)=-100 | | -y=2x | | y=(-2/3)x+1 | | 296-6x=39x+24 | | -5x-15=6x+18 | | 3z=16-34 | | 20=4(x+-3) | | -10y+18=-3(5-7)+5y | | -34-9x=49-30 | | -y=18-6x | | 2xcm= | | (4x-5)=(x) | | 3/4+3/5 |